Buckling Analysis of Functionally Graded Annular Spherical Shells and Segments Subjected to Mechanic Loads - Bich, Dao Huy; Phuong, Nguyen Thi (VNU Journal of Science: Mathematics - Physics; Vol 29 No 3, 2013)
Abstract: An analytical approach is presented to investigate the buckling of functionally graded annular spherical segments subjected to compressive load and radial pressure. Based on the classical thin shell theory, the governing equations of functionally graded annular spherical segments are derived. Approximate solutions are assumed to satisfy the simply supported boundary condition of segments and Galerkin method is applied to obtain closed-form relations of bifurcation type of buckling loads. Numerical results are given to evaluate effects of inhomogeneous and dimensional parameters to the buckling of structure. Keywords: Functionally graded material; annular spherical segment; critical buckling load.